'Should we ask the students' opinions first?' Practice architectures of student participation from the perspective of teachers. (November 2021) - Niemi, Reetta; Loukomies, Anni
An in-service training programme was used as an accelerator that scaffolded teachers in four school units in Lappeenranta, Finland, the aim being to find a shared understanding and shared practices, or 'praxis', in terms of promoting student participation. In this study we examine the practices that either supported or prevented participation from the perspective of the teachers. We also examine how the arrangements of the practice architectures – cultural-discursive, material-economic and social-political – appear in the teachers' accounts of student participation. The data consists of 22 diamond-ranking forms made by 86 teachers, and an audio-recorded and videotaped group interview. The teachers in the school units found praxis both in the support of student participation (emphasising the students' role in school councils and giving them a recognised role in everyday practices) and in the challenges (turning participation into pedagogical practice). The arrangements of the practice architectures were identified in the group interview.